STUDI ETNOMATEMATIKA PADA AKTIVITAS PENGRAJIN TEMBOLAK MASYARAKAT LOMBOK TIMUR - Solehah, Irfani; Kusaeri, Al; Hardiani, Nur (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to examine ethnomathematical elements found in the activities of tembolak craftsmen in East Lombok society. This research employed a qualitative method with an ethnographic approach and was conducted in Peresak Village, Sakra District, East Lombok Regency. Data were collected through observations and in-depth interviews with tembolak craftsmen, and data validity was ensured through source triangulation. The findings indicate that mathematical objects emerging in the tembolak crafting process include plane figures, such as quadrilaterals and circles, as well as solid figures in the form of a hemisphere. The identified mathematical activities include measuring, arranging, repeating, and systematically shaping materials. Furthermore, the mathematical concepts involved encompass geometry, measurement, and traditional number systems. Based on the results of observations and interviews, mathematical objects, mathematical activities, and mathematical concepts in the tembolak making process are interconnected and form a coherent whole. These findings indicate that tembolak crafting activities can be utilized as a meaningful and contextual learning context for junior high school mathematics based on local culture